The Urgency Of Political Education For Young Generation In Indonesia - Wijayanto Said, Ridwan (Jurnal Syntax Fusion, 2023)
The younger generation, or millennials, are made up of people between the ages of 24 and 39. Members of this generation have been assigned to vote in various parliamentary elections. Millennials are a powerful force ahead of general elections in 2024 that will enable political and party elites to win their seats in parliament and power. As a result, we provide knowledge to first-time voters through outreach and political literacy. First-time voters learn a lot from this activity, which helps them make informed decisions and avoid being swayed by political misinformation.